Implementing 802.11 with microcontrollers : - Eady, Fred (Elsevier/Newnes, 2005)
Wireless networking is poised to have a massive impact on communications, and the 802.11 standard is to wireless networking what Ethernet is to wired networking. There are already over 50 million devices using the dominant IEEE 802.11 (essentially wireless Ethernet) standard, with astronomical growth predicted over the next 10 years. New applications are emerging every day, with wireless capability being embedded in everything from electric meters to hospital patient tracking systems to security devices. This practical reference guides readers through the wireless technology forest, giving them the knowledge, the hardware and the software necessary to design a wireless embedded device rapidly, inexpensively, and effectively. Using off-the-shelf microcontrollers from Microchip and Atmel, the author provides step-by-step instructions for designing the hardware and firmware for a fully operational wireless networking device. The book gives a thorough introduction to 802.11 technology and puts it into perspective against the other wireless standard options. Just enough theory and mathematics is provided to give the depth of understanding needed for practical design work.